2018
DOI: 10.1029/2018pa003408
|View full text |Cite
|
Sign up to set email alerts
|

Data Constraints on Glacial Atlantic Water Mass Geometry and Properties

Abstract: The chemical composition of benthic foraminifera from marine sediment cores provides information on how glacial subsurface water properties differed from modern, but separating the influence of changes in the origin and end‐member properties of subsurface water from changes in flows and mixing is challenging. Spatial gaps in coverage of glacial data add to the uncertainty. Here we present new data from cores collected from the Demerara Rise in the western tropical North Atlantic, including cores from the moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 137 publications
(286 reference statements)
11
84
1
Order By: Relevance
“…Painstaking efforts have been devoted to reconstruct changes in AMOC dynamics in the recent geological past in order to better predict its future evolution. These investigations provide ample evidence for large-scale glacial and deglacial AMOC reorganizations as inferred from independent proxy approaches (Howe, Piotrowski, Noble, et al, 2016;Lippold et al, 2016;Lynch-Stieglitz, 2017;Marchitto & Broecker, 2006;McManus et al, 1999;Oppo et al, 2018;Praetorius et al, 2008;Roberts et al, 2010). While there is a general sense that AMOC variability was subdued during the Holocene compared with the last glacial termination (Keigwin & Boyle, 2000;Oppo et al, 2003), proxy evidence is often contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Painstaking efforts have been devoted to reconstruct changes in AMOC dynamics in the recent geological past in order to better predict its future evolution. These investigations provide ample evidence for large-scale glacial and deglacial AMOC reorganizations as inferred from independent proxy approaches (Howe, Piotrowski, Noble, et al, 2016;Lippold et al, 2016;Lynch-Stieglitz, 2017;Marchitto & Broecker, 2006;McManus et al, 1999;Oppo et al, 2018;Praetorius et al, 2008;Roberts et al, 2010). While there is a general sense that AMOC variability was subdued during the Holocene compared with the last glacial termination (Keigwin & Boyle, 2000;Oppo et al, 2003), proxy evidence is often contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Today, these sites are located just below the low salinity core of Antarctic Intermediate Waters (AAIW) and within the mixing gradient with high salinity NADW (supporting information Figure S1). Concentrations of PO 4 and Cd are elevated in AAIW relative to NADW (Middag et al, ; Figure ), in part because Circumpolar Deep Water (CDW) contributes nutrients to AAIW (Sarmiento et al, ) and in part because remineralization in the AAIW formation region increases the PO 4 values and reduces δ 13 C values (Oppo et al, ). Middepth sediment core PC‐CAM61 (22.52°S, 39.90°W) was collected from 1,890‐m water depth, within the modern extent of NADW and near its upper boundary with AAIW.…”
Section: Introductionmentioning
confidence: 99%
“…Stable carbon isotope data (δ 13 C) from a depth transect along the BBOR show lighter δ 13 C values with increasing water depth interpreted as propagating SSW during the LGM (Evans & Hall, ; Keigwin, ). However, in the light of recent findings of past water mass distributions in the western Atlantic basin from a δ 13 C and Nd isotope perspective, an extensive advance of SSW into the North Atlantic may need to be seen more critically (Gebbie, ; Howe et al, ; Oppo et al, ; Spooner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Spooner et al () therefore suggested that the boundary between GNAIW and SSW at 30°S was situated somewhere between 2,600‐ and ~4,000‐m water depth possibly in deeper than in shallow depths. This boundary is rather expected to descend toward 30°N instead of being stable on such a long distance due to the increasing dominance of NSW with shorter distance to the NADW formation areas (Gebbie, ; Howe et al, ; Oppo et al, ). Accordingly, a strong inflow of SSW in the deep northwestern Atlantic basin during the LGM appears unlikely.…”
Section: Discussionmentioning
confidence: 99%